METHOTREXATE FOR REBOUND PHENOMENON OF VOGT-KOYANAGI-HARADA IN JUVENILE: A RARE CASE REPORT - Bachmid, Humairah; Eka, Hasnah; Anoez, Azizah; Fikri, Bahrul (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Vogt-Koyanagi-Harada (VKH), an auto-immune disorder driven by melanocyte antigen, is rare in children. The mainstay treatments are corticosteroid and immunomodulators. Methotrexate is one of immunomodulator that widely used due to its effectiveness with minimal side effects. Case Report: A 9-years-old boy get diagnosed Vogt-Koyanagi-Harada. His best corrected visual acuities (BCVA) were 20/400 in both eyes. Anterior segment examination showed granulomatous uveitis. Posterior segment examination revealed optic disk swelling, Dallen Fuch’s nodule and exudative retinal detachment. We also found poliosis and vitiligo in his lips. He had been previously treated with topical corticosteroids, oral corticosteroids and topical cycloplegics. The dose was tapered every month. After taking medication for 5 months with the last dose oral corticosteroid 16 mg/day and topical corticosteroid every 8 hours, his BCVA recovered to 20/25 RE and 20/40 LE. During the treatment time, the patient discontinued the medication due to parental disobedience and then came with decrease of vision. Based on the consideration of rebound phenomenon and the use of maximum dose of corticosteroids, we consulted the patient to the pediatrician, and decided to give methotrexate as an immunosuppressant. After receiving 15 mg/week of methotrexate for 3 months, inflammation calmed down but unfortunately the vision did not improve. Discussion: In children, the main treatment for VKH disease is high-dose corticosteroids. Considering the side effects of prolonged systemic corticosteroid therapy, methotrexate become the first line of corticosteroid sparing agent, especially in chronic stage. Conclusion: Methotrexate can be an effective treatment option for rebound VKH. Keywords: Juvenile Vogt-Koyanagi-Harada, Steroid Sparing Agents, Rebound Phenomenon, Methotrexate.